Importance of complement 3 and mannose receptors in phagocytosis of paracoccidioides brasiliensis conidia by macrophages lines (2006)
ABSTRACT : Genetic factors influence susceptibility to aracoccidioidomycosis, a Latin American endemic mycosis. The pattern of susceptibility of congenic mouse strains infected with Paracoccidioides brasiliensis resembles the pattern of the Nramp1 gene. Thus, congenic murine bone-marrow-derived macrophage lines B10R (Nramp1rGly169) and B10S (null Nramp1 protein expression, Nramp1sAsp169) were infected with P. brasiliensis conidia and compared, under opsonic and nonopsonic conditions. Opsonization increased the percentage of phagocytosis by both cell lines. B10R macrophages exhibited a higher percentage of cells with associated conidia and higher number of conidia per macrophage than B10S. Heat-inactivation and EDTA treatment of serum used for opsonization, and treatment of macrophages with anti-complement receptor 3 (CR3) decreased phagocytosis by both cell lines. a-methyl-D-mannoside reduced phagocytosis by B10R macrophages, suggesting that the mannose receptor participates in phagocytosis by these cells. The CR3 expression was similar on both cell lines and B10R expressed more mannose receptors, but neither cell line expressed CR1. IFNg decreased the conversion of conidia to the yeast form of P. brasiliensis in B10R, but not in B10S macrophages.